Severe Case of Oral Baclofen Withdrawal Resulting in Mechanical Ventilation - Resha Khanal; Sharad Oli; Janet Chan Gomez; Sahar Tahir; Binita Bhandari; Saketram Komanduri (SAGE Publishing, 2022)
Abrupt baclofen withdrawal may be life-threatening with varied neuropsychiatric manifestations. We present a case of baclofen withdrawal necessitating intubation. A 58-year-old female with a history of undiagnosed muscle spasticity presented with worsening extremities tremors, paresthesia, and weakness for 2 days. Initial vitals included temperature 103 F, tachycardia, hypertension, and tachypnea. Examination revealed coarse tremors of all extremities. Inflammatory markers, blood, and urine culture were negative. Head and spine imaging were non-diagnostic. Meningitis and seizure were ruled out. She continued worsening with hallucinations, hyperpyrexia, ocular clonus, and profound muscle rigidity. The patient was intubated for respiratory distress and transferred to intensive care unit (ICU). Further history revealed running out of oral baclofen 3 days ago. Baclofen was restarted with symptomatic improvement. The patient was extubated after 2 days and discharged to a rehabilitation facility. Oral or intrathecal baclofen is thought to inhibit spinal nerves reducing muscle spasm and pain. Abrupt stoppage causes activation of dopamine and noradrenergic receptors causing muscle spasms, tremors, hyperpyrexia, delusions, hallucination, and delirium. Severe cases can mimic meningoencephalitis, seizure disorder, or neuroleptic malignant syndrome. Symptoms usually develop in 1 to 3 days of cessation and can be life-threatening if unrecognized timely. Treatment includes supportive therapy, re-administration of baclofen, or use of benzodiazepines, propofol, dexmedetomidine; however, no specific guidelines have been established. To the knowledge of the authors, this is the first case of oral baclofen withdrawal requiring intubation. We found only 3 reported cases of intrathecal baclofen withdrawal necessitating intubation.